Opinion of the Farmers Regarding mobile based Agro-advisory Service - Sidhu, Harmandeep Kaur; Garg, Lavleesh (Indian Journal of Extension Education, 2017)
Mobile based agro-advisories have been deployed by many organisations. the present study conducted in Jalandhar  district of Punjab. It revealed that mobile assisted extension services led to higher degree of satisfaction about information  among the farmers.
Keywords: Mobile Based Agro-advisory